Photoprotective and antioxidant effects of Rhubarb: Inhibitory action on tyrosinase and tyrosine kinase activities and TNF-α, IL-1α and α-MSH production in human melanocytes - Silveira, Jéssica P.S. [UNESP]; Seito, Leonardo N. [UNESP]; Eberlin, Samara; Dieamant, Gustavo C.; Nogueira, Cecília; Pereda, Maria C.V.; Di Stasi, Luiz C. [UNESP] (Springer Nature, 2013)
Background: Exposure to ultraviolet (UV) radiation causes various forms of acute and chronic skin damage, including immunosuppression, inflammation, premature aging and photodamage. Furthermore, it induces the generation of reactive oxygen species, produces proinflammatory cytokines and melanocyte-stimulating hormone (MSH) and increases tyrosinase activity. The aim of this study was to evaluate the potential photoprotective effects of Rheum rhaponticum L. rhizome extract on human UV-stimulated melanocytes.Methods: The effects of Rheum rhaponticum rhizome extract on tyrosine kinase activity, and on interleukin-1α (IL-1α), tumour necrosis factor α (TNF-α), and α-MSH production in human epidermal melanocytes were evaluated under UV-stimulated and non-stimulated conditions. Antioxidant activity was evaluated by lipid peroxidation and 1,1-dyphenyl-2-picryl-hydrazyl (DPPH) assays, while anti-tyrosinase activity was evaluated by the mushroom tyrosinase method.Results: Rheum rhaponticum L. rhizome extract showed in vitro antioxidant properties against lipid peroxidation, free radical scavenging and anti-tyrosinase activities, and inhibited the production of IL-1α, TNF-α, α-MSH, and tyrosine kinase activity in melanocytes subjected to UV radiation.Conclusions: These results support the inclusion of Rheum rhaponticum L. rhizome extract into cosmetic, sunscreen and skin care products for the prevention or reduction of photodamage. © 2013 Silveira et al; licensee BioMed Central Ltd.
Keywords: α-MSH; Melanocytes; Photoprotection; Rheum rhaponticum; Skin-lightening; UV radiation; 1,1 diphenyl 2 picrylhydrazyl; alpha intermedin; interleukin 1alpha; lipid; monophenol monooxygenase; protein tyrosine kinase; rhubarb extract; tumor necrosis factor alpha; antioxidant activity; controlled study; cytokine production; drug effect; enzyme activity; enzyme inhibition; human; human cell; in vitro study; lipid peroxidation; melanocyte; radiation protection; rheum rhaponticum; rhubarb; skin protection; ultraviolet radiation; alpha-MSH; Antioxidants; Biphenyl Compounds; Cytokines; Enzyme Inhibitors; Free Radical Scavengers; Humans; Inflammation Mediators; Interleukin-1alpha; Lipid Peroxidation; Monophenol Monooxygenase; Phytotherapy; Picrates; Plant Extracts; Protein-Tyrosine Kinases; Rheum; Rhizome; Skin; Skin Diseases; Tumor Necrosis Factor-alpha; Ultraviolet Rays